Intratumoral Haemorrhage Causing an Unusual Clinical Presentation of a Vestibular Schwannoma. Issue 1 (1st February 2013) - Gagliardo, C.; Martines, F.; Bencivinni, F.; La Tona, G.; Lo Casto, A.; Midiri, M.
We present a case of an elderly woman with no history of audiological disease with sudden onset of visual and hearing deficits associated with systemic clinical signs. On examination she had impairment of right CNs from V to X. CT and MR imaging demonstrated a cystic vestibular schwannoma with a rare intralesional fluid-fluid level correlated to a recent bleed. We include high quality MR images to show the acute impairment of the cranial nerves next to the tumour after acute bleeding. Our case report includes a voxel-based morphometry (VMB) analysis of the tumour that, as far as we know, has never been done before for such a tumour. VBM analysis was performed to calculate the hypothesized volume changes after the acute bleed which likely resulted in a sudden increase in the overall size of the tumour resulting in atypical clinical signs and symptoms due to the establishment of a mechanical conflict with the adjacent cranial nerves.